R-type Ca(2+)-channel-evoked CICR regulates glucose-induced somatostatin secretion. - Zhang, Q; Bengtsson, M; Partridge, C; Salehi, A; Braun, M; Cox, R; Eliasson, L; Johnson, P; Renström, E; Schneider, T; Berggren, P; Göpel, S; et al. (2007)
Pancreatic islets have a central role in blood glucose homeostasis. In addition to insulin-producing beta-cells and glucagon-secreting alpha-cells, the islets contain somatostatin-releasing delta-cells. Somatostatin is a powerful inhibitor of insulin and glucagon secretion. It is normally secreted in response to glucose and there is evidence suggesting its release becomes perturbed in diabetes. Little is known about the control of somatostatin release. Closure of ATP-regulated K(+)-channels (K(ATP)-channels) and a depolarization-evoked increase in cytoplasmic free Ca(2+) concentration ([Ca(2+)](i)) have been proposed to be essential. Here, we report that somatostatin release evoked by high glucose (>or=10 mM) is unaffected by the K(ATP)-channel activator diazoxide and proceeds normally in K(ATP)-channel-deficient islets. Glucose-induced somatostatin secretion is instead primarily dependent on Ca(2+)-induced Ca(2+)-release (CICR). This constitutes a novel mechanism for K(ATP)-channel-independent metabolic control of pancreatic hormone secretion.